Increased serum amylase and/or lipase in coronavirus disease 2019 (COVID‐19) patients: Is it really pancreatic injury?. Issue 2 (28th December 2020) - Pribadi, Rabbinu R; Simadibrata, Marcellus
Abstract: Coronavirus disease 2019 (COVID‐19) is a novel disorder caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Although it mainly affects the respiratory system, the pancreas could also become the virus' target. The issue regarding pancreatic involvement in COVID‐19 has been raised by several researchers. They found increased serum amylase and/or lipase in COVID‐19 patients, which suggested pancreatic injury. We aimed to critically review the evidence to provide insights and to answer the very question of the possibility of pancreatic injury. Current evidence shows that increased amylase and/or lipase is not necessarily a pancreatic injury in COVID‐19 patients. Those increased enzymes might also be found in other clinical conditions. Abstract : Coronavirus disease 2019 (COVID‐19) is a novel disorder caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Although it mainly affects respiratory system, the issue regarding pancreatic involvement in COVID‐19 has been raised by several researchers. Current evidence shows that increased serum amylase and/or lipase is not necessarily an indicator of pancreatic injury in COVID‐19 patients. Those increased enzymes might also be found in other clinical conditions.